Writing Spaces Readings on Writing Vol. II - Lowe, Charlie; Zemliansky, Pavel (Open textbook library., 2011)
Volumes in Writing Spaces: Readings on Writing offer multiple perspectives on a wide-range of topics about writing. In each chapter, authors present their unique views, insights, and strategies for writing by addressing the undergraduate reader directly. Drawing on their own experiences, these teachers-as-writers invite students to join in the larger conversation about the craft of writing. Consequently, each essay functions as a standalone text that can easily complement other selected readings in writing or writing-intensive courses across the disciplines at any level. Volume 2 continues the tradition of the previous volume with topics, such as the rhetorical situation, collaboration, documentation styles, weblogs, invention, writing assignment interpretation, reading critically, information literacy, ethnography, interviewing, argument, document design, and source integration.